Antioxidant and prooxidant activities of phenolic acids commonly existed in vegetables and their relationship with structures - GAO,Qingchao (2022)
Abstract Phenolic acids existed in many agricultural products especially in vegetables and considered as important natural antioxidants. Eleven phenolic acids existed commonly in vegetables were chosen to assess the antioxidant activities using DPPH·, ·ABTS+, ·O2-, and ·OH scavenging assays, as well as ferric reducing power and β-carotene bleaching assays. The results showed that caffeic and protocatechuic acid with simple dihydroxylation structures have the best antioxidant activities, while p-Hydroxybenzoic and p-Coumaric acid with mono hydroxylation structures have the lowest antioxidant activities in most assays. The antioxidant activity of caffeic acid was higher than protocatechuic acid and ferulic acid higher than isoferulic acid may be due to the substituents and the position of substituents on the benzene ring. Antioxidant activities of caftaric, chicoric and chlorogenic acid and its derivates with complex dihydroxylation structures were high relatively among phenolic acids. The different concentration ranges of phenolic acids were obtained based on the quantitative relationship between antioxidant or prooxidant activities and sample concentrations. The prooxidant effect of phenolic acids was rarely observed in the present study. The results were conducive to further research on potential biological activities of vegetables.